The porphobilinogen deamise - uroporphyrinogen III cosynthetase system (porphobilinogenase) from bovine liver. Kinetic studies - Sancovich, H.A. (1969)
Fil:Sancovich, H.A. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.